Linear quadratic regulator (LQR) approach for lifting and stabilizing of two wheeled wheelchair - Ahmad, Salmiah; Tokhi, M. Osman (2011)
This paper discussed about the implementation of Linear Quadratic Regulator (LQR) on a two-wheeled wheelchair model. The state space model of the two-wheeled wheelchair that mimics double inverted pendulum has been obtained from the linearized mathematical equations of the model. The equations of motions, which are very complex, are derived from the wheels, Link1 and Link2. The goal is to have both links of the two-wheeled wheelchair to be at the upright position. To fulfill the goal, Link1 is to be lifted up from its initial position to zero degree upright position while maintaining Link2 at the upright position. This research is aimed to help disabled people who are using the wheelchair as the main transport for mobility but cannot stand on his own due to permanent injuries on the extremities. The scenario requires a suitable control strategy for the good system performance. Results show that LQR provides good response with the linearized differential equations.